Phytochemical investigation of Piper betle Linne (Family Piperaceae) - Regis, Reginaldo S.
The leaves of Piper betle Linne (Family Piperaceae) were chosen as the plant material for investigation. Different periods of collection or plucking were conducted to prepare for the moisture content determination, using the Cencobalance, utilizing leaves dried for 18 days, leaves dried for 3 days, and the fresh young leaves of Piper betle.